A Qualitative Study on the Perspectives of Latinas Enrolled in a Diabetes Prevention Program: Is the Cost of Prevention Too High?. (August 2020) - Joachim-Célestin, Maud; Gamboa-Maldonado, Thelma; Dos Santos, Hildemar; Montgomery, Susanne B.
Introduction: Latinas are among the groups most affected by diabetes health disparities, yet they often benefit less from diabetes interventions even when these are culturally adapted. The purpose of this qualitative study was to explore readiness of Latinas enrolled in a diabetes prevention program to adopt recommended preventive behaviors, and to identify factors associated with the adoption and maintenance of these recommended lifestyle changes. Insights gained will be used to inform future efforts at reducing diabetes disparities and the burden of chronic diseases among Latinas.Methods: Nine focus group discussions (FGDs) and 3 key informant interviews (KIIs) were conducted after the completion of a culturally adapted diabetes prevention program led by Latino community health workers. A grounded theory approach by Charmaz informed by the transtheoretical model guided the questions. Discussions and interviews were audio-taped with participants' permission, transcribed, coded, and themed.Results: Forty low-income Latinas contributed to FGDs and KIIs. Baseline readiness to engage in new behaviors varied. Negative personal and family health events and physician referral impacted most readiness to enroll and to adopt preventive behaviors. Built environment, financial constraints, and threat of social alienation constituted major barriers to behavior adoption and maintenance, while physician involvement, awareness of diabetes complications, and social support partially mitigated these impediments.Conclusions: Our results suggest that timing of enrollment, physician-patient dynamics, and the emotional personal/family cost of behavior modification should all be considered when planning diabetes prevention programs for low-income Latinas. Besides appropriately timing referrals to accessible culturally informed prevention programs, health educators and health care providers should be aware of the potentially negative impact of behavior modification on family dynamics and be prepared to address resulting repercussions. Future research on Latinas should also include and report data on physician involvement, family context, and social determinants of health for more consistent program comparisons.